A Cross-Sectional Study of the Impact of Standardized Tobacco Packaging Legislation on University Students. Issue 3 (4th May 2018) - Poundall, Thomas; Bogdanovica, Ilze; Langley, Tessa
ABSTRACT: Background : European Union and national legislation implemented from May 2016 mean that from May 2017 all tobacco products in the United Kingdom must be sold in standardized packs without external branding and with prominent graphic health warnings. This study investigates the level of awareness and acceptability of the legislation in students during the implementation period, and how the legislation may impact on student perceptions of pack attributes, health warning effectiveness, student smokers' willingness to pay for cigarette packs, and intentions to quit. Methods : An online survey link was e-mailed to randomly selected University of Nottingham students in autumn 2016. Descriptive statistics and multivariate logistic regression models were used to investigate awareness, acceptability, and potential quitting behavior. Results : 546 students (175 smokers, 371 nonsmokers) responded. Very few of students had seen a standardized pack. Smokers were more likely to be aware of the new legislation than non-smokers. More smokers noticed the warnings on standardized packs than on branded ones. Fewer smokers were willing to pay current prices for standardized packs than for 20 branded packs. Just under half of smokers anticipated quitting in response to the new legislation, with those who smoke infrequently being more likely to anticipate quitting than daily smokers. Conclusions : Few students had seen a standardized pack, suggesting that the level of implementation of the legislation was low five to six months into the implementation period. However, the findings suggest that the legislation has the potential to increase quitting behavior in smoking students.